Alinhamento de valores pessoais e organizacionais: um estudo de caso em empresa de médio porte - Limeira, Maria Ignez Carneiro de Azevedo (2004)
This research proposes to investigate which values permeate the corporate culture of the company that is being studied, in which consciousness level they are, and if there is alignment among them. It was adopted as main theoretical reference for the work, the consciousness levels theory of Richard Barret (2000), who has expanded the hierarchical needs theory of Abraham Maslow (1999) to higher levels. The bibliographic revision dissertates about personal and corporate values and organizational culture, putting in evidence the importance of the leadership role in its formation and development process. In order to collect the research information, a structured questionnaire was applied, as the main tool. Beyond this, participant observation and documentation analyses were conducted, so as to construct an evaluation methodology that facilitate the necessary actions planning, having as base the organization diagnosis about the alignment between personal and organizational values. The results were presented in tables and figures, and showed the distribution of all values among the seven levels of consciousness, as well as, showed those considered as the most important ones, and the positive and boundary ones, for all the group together and for the executives group and the employees one, separately. The conclusions pointed to little alignment between personal and organizational values within the company, and the recommendations have the objective of suggesting priority actions linked to the obtained results, and other studies about the theme